Small molecule RORγt antagonists inhibit T helper 17 cell transcriptional network by divergent mechanisms - Xiao, Sheng (2014)
We identified three RORγt-specific inhibitors that suppress T helper 17 (Th17) cell responses including Th17 cell-mediated autoimmune disease. We systemically characterized RORγt binding in the presence and absence of drug with corresponding whole-genome transcriptome sequencing. RORγt acts both as a direct activator of Th17 cell signature genes and as a direct repressor of signature genes from other T-cell lineages, with the strongest transcriptional effects on cis-regulatory sites containing the RORα binding motif. RORγt is central in a densely interconnected regulatory network that shapes the balance of T-cell differentiation. The three inhibitors identified here modulated the RORγt-dependent transcriptional network to varying extents and through distinct mechanisms. Whereas one inhibitor displaced RORγt from its target-loci, the two more potent inhibitors affected transcription predominantly without removing DNA-binding. Our work illustrates the power of a system-scale analysis of transcriptional regulation to characterize potential therapeutic compounds that inhibit pathogenic Th17 cells and suppress autoimmunity.